Evaluation of extended thymectomy approaches based on residual fat tissue. (24th November 2020) - Yoshida, Mitsuteru; Yuasa, Masao; Kondo, Kazuya; Tsuboi, Mitsuhiro; Kawakita, Naoya; Tangoku, Akira
Abstract: OBJECTIVES: This study analysed the patterns of extraction ranges, characteristics, advantages and disadvantages of median sternotomy (MS) and subxiphoid (SX) approaches for extended thymectomy. METHODS: This study included patients with anterior mediastinum tumour and myasthenia gravis who underwent extended thymectomy at our institution between 2015 and 2018. There were 5 MS and 6 SX extended thymectomy surgeries with the VINCENT software. On preoperative computed tomography, the thymus area and fat tissue surrounding the thymus, which were planned for extraction, were traced using VINCENT (Ver. 4.0). We then constructed three-dimensional images and calculated the volumes. Evaluation of the extended thymectomy approach based on the residual fat tissue was required to determine the area of extended thymectomy. RESULTS: No significant differences in operation time (min) [SX: 197.3 ± 34.0, MS: 206.6 ± 91.4, drainage duration (days), SX: 2.2 ± 1.0, MS: 2.2 ± 0.4, hospital stay (days), SX: 11.8 ± 1.2, MS: 13.4 ± 2.1, residual rate (%), SX: 29.9 ± 17.5, MS: 58.7 ± 18.0 ( P = 0.0519)] were observed between the 2 groups. Bleeding was significantly lower for SX than for MS. The residual rate was lower for SX than for MS. CONCLUSIONS: Considering the amount of the residual fat tissue, the SX approach allows an adequate dissection area for extended thymectomy compared with the MS approach. Abstract : Median sternotomy (MS) and subxiphoid (SX) approaches are the conventional surgical procedures for extended thymectomy, and endoscopic surgical techniques also have expanded in recent years.